INCLUSIVE EDUCATION AND LOCAL WISDOM: CREATING A FRIENDLY LEARNING ENVIRONMENT FOR CHILDREN WITH SPECIAL NEEDS - Novianty Djafri; Ceiezta Korlefura; Mustopa (CV. ADIBA ASIHA AMIRA, 2024)
Inclusive education is one of the strategic efforts in providing equal access for children with special needs to thrive in an educational environment. The link between inclusive education and local intelligence can bridge the gap between meeting special education needs and exploiting local potential. The study aims to identify and analyse how inclusive education based on local wisdom can create an enabling and supportive learning environment for the growth and development of students with special needs. Through literary research methods, this research collects and analyzes data from various scientific publications, research reports, and related educational documents. Research findings show that integrating inclusive education with local wisdom can raise community awareness, increase curriculum relevance, and strengthen social support for children with special needs.